Inovasi Pembuatan Briket dari Bonggol Jagung (Zea Mays L.) sebagai Pengusir Nyamuk dan Aromaterapi Alami - Rahmadani, Arini Dwi; ., Susilawati; Sari, Dinda Purnama; Rambe, Raudhiyah Hasanah; Sari, Nailla Deswita (Jurnal Sains dan Teknologi (JSIT), 2026)
Corn cobs (Zea mays L.) are a type of agricultural waste that has the potential to pollute the environment if not utilized optimally, even though they contain carbon that can be processed into biomass briquettes. This study aims to develop an innovation in the production of briquettes from corn cobs that function as an alternative energy source as well as a natural aromatherapy and mosquito repellent through the addition of lemongrass oil. The research method used a descriptive approach through a pilot study that included the process of corn cob carbonization, charcoal grinding and sieving, mixing with tapioca glue and lemongrass oil, molding, and briquette drying, with observational evaluation of physical characteristics and combustion behavior without controlled laboratory testing. The results showed that variations in material composition affected the physical characteristics and combustion performance of the briquettes. A formulation with a 20:2:1 ratio of corn cob charcoal powder, tapioca adhesive, and lemongrass oil produced briquettes with good density, resistance to cracking, relatively little ash and smoke, and a herbal aroma during combustion. The briquettes also showed potential in reducing the presence of mosquitoes around the area of use. This research has implications for the utilization of agricultural waste as an environmentally friendly product that has functional added value and has the potential to support the development of biomass-based alternative energy.